Arena Simulation Training Guideline for Assembly Line - Maslazim, Norsahira; Sh Ahmad, Sh Salleh (Research Progress in Mechanical and Manufacturing Engineering, 2022)
As a beginner for the software that unfamiliar with us to handle this like Arena Simulation software it’s a bit tough when we need to do a simple model by referring to the textbooks or article journal that contains a lot of difficult words to understand. Therefore, the guideline was created to solve this problem that contains a simple word, more infographic and the simple step by step that easy to follow, understand and it helps a lot for the users. The purpose of the study was to build a training guideline for modeling an assembly line by using Arena Simulation, to build a model representing the assembly process using the training guide, and analyze the simulation result for the assembly line model. The study was conducted using Arena Simulation software. The data was collected based on the actual model to be inserted into the system setting for validation purposes. The model was created with 32 hours’ replications length to achieve accuracy in the result. The difference between the actual and simulation model must below 5% percent to said the data is valid. To verify the guideline is correct we need to do another example of the model and comparison the data with the actual data from the textbooks. To validate the data, we need to calculate the percentage difference between the actual and simulation model data. This simulation finding could be a guideline for the next generations to make any improvement in the guideline. To conclude, Arena simulation software is a powerful discrete event simulation that mimics the real situation in the production line.